1996
DOI: 10.1016/s0741-5214(96)70282-3
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of focal aortic arch branch lesions with Palmaz stents

Abstract: Focal aortic branch lesions can be effectively and safely treated with Palmaz stents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(46 citation statements)
references
References 15 publications
1
42
1
2
Order By: Relevance
“…Stenting was subsequently introduced to address these issues and theoretically reduce the risk of atheroembolization. Recent experiences of PTA and stenting treatment of the innominate artery lesions, performed in other center, with short and midterm results, suggest that percutaneous treatment of the innominate arteries can be performed with relatively safety and expectations of satisfactory mid-term success [6,[9][10][11][12]18,19]. In our experience the access to innominate artery lesion was achieved in a retrograde fashion via a humeral right artery puncture.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Stenting was subsequently introduced to address these issues and theoretically reduce the risk of atheroembolization. Recent experiences of PTA and stenting treatment of the innominate artery lesions, performed in other center, with short and midterm results, suggest that percutaneous treatment of the innominate arteries can be performed with relatively safety and expectations of satisfactory mid-term success [6,[9][10][11][12]18,19]. In our experience the access to innominate artery lesion was achieved in a retrograde fashion via a humeral right artery puncture.…”
Section: Discussionmentioning
confidence: 75%
“…Initially these lesions were treated with PTA alone [6][7][8][9][10][11][12][13], but subsequent studies have reported an improvement in these initial results when stenting implantation was associated to balloon angioplasty [11,[14][15][16][17]. Recent reports, with short and midterm results, suggest that percutaneous treatment of the innominate arteries can be performed with relatively safety and expectations of satisfactory mid-term success [6,[9][10][11][12]18,19]. In our Center we have performed 6 procedures of PTA and stenting for stenotic and occlusive innominate artery lesions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the literature on the endovascular or hybrid open treatment of the IA is limited and consists only of small series with short clinical follow-ups. 1,[6][7][8][9][10] Furthermore, most of the series did not focus on the treatment of IA stenosis alone but combined the outcomes of the treatment of vertebral, subclavian, and carotid arteries.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Standard open surgical procedures are now mostly reserved for extensive multivessel involvement or after failed endovascular procedures.…”
mentioning
confidence: 99%
See 1 more Smart Citation